The microbiota influences the Drosophila melanogaster life history strategy - Amber W. Walters; Rachel C. Hughes; Tanner B. Call; Carson J. Walker; Hailey Wilcox; Samara C. Petersen; Seth M. Rudman; Peter D. Newell; Angela E. Douglas; Paul S. Schmidt; John M. Chaston (Molecular Ecology, 2020)
Organisms are locally adapted when members of a population have a fitness advantage in one location relative to conspecifics in other geographies. For example, across latitudinal gradients, some organisms may trade off between traits that maximize fitness components in one, but not both, of somatic maintenance or reproductive output. Latitudinal gradients in life history strategies are traditionally attributed to environmental selection on an animal's genotype, without any consideration of the possible impact of associated microorganisms (“microbiota”) on life history traits. Here, we show in Drosophila melanogaster , a key model for studying local adaptation and life history strategy, that excluding the microbiota from definitions of local adaptation is a major shortfall. First, we reveal that an isogenic fly line reared with different bacteria varies the investment in early reproduction versus somatic maintenance. Next, we show that in wild fruit flies, the abundance of these same bacteria was correlated with the latitude and life history strategy of the flies, suggesting geographic specificity of the microbiota composition. Variation in microbiota composition of locally adapted D. melanogaster could be attributed to both the wild environment and host genetic selection. Finally, by eliminating or manipulating the microbiota of fly lines collected across a latitudinal gradient, we reveal that host genotype contributes to latitude‐specific life history traits independent of the microbiota and that variation in the microbiota can suppress or reverse the differences between locally adapted fly lines. Together, these findings establish the microbiota composition of a model animal as an essential consideration in local adaptation.